Implementation of STEAM Learning Using Loose Parts Materials to Develop Early Childhood Cognitive Skills - Eny Isnariyati (Journal of Islamic Education Students (JIES), 2024)
This study aims to examine the effect of implementing STEAM-based learning using loose parts materials on the development of cognitive and artistic skills in early childhood. The research employed a quantitative approach with a Quasi-Experimental design. The study involved 53 children from TK DWP Tawangsari Sidoarjo, divided into two groups: the experimental group and the control group. Data were collected through direct observation using standardized test instruments that measured logical thinking, problem-solving, creativity, as well as the ability to assemble and create new shapes. The results of data analysis, using t-tests to assess significance, indicated that learning with loose parts significantly improved children's cognitive and artistic skills.